2016
DOI: 10.15517/rbt.v64i2.18575
|View full text |Cite
|
Sign up to set email alerts
|

Seed colour affects light and temperature requirements during germination in two Lotus species (Fabaceae) of the Arabian subtropical deserts

Abstract: Heterogeneity in seeds mostly occurs due to physiological, environmental and genetic factors, and these could affect seed dormancy and germination. Therefore, the aim of our study was to assess the effect of seed colour on germination behavior. For this, both light and temperature requirements were assessed in Lotus glinoides and Lotus halophilus (Fabaceae) from the hyper-arid deserts of the United Arab Emirates. Germination was assessed in terms of both final germination level (percentage) and germination rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Seeds from dark-developed capsules have not only a difference in mass but also in their tendency to germinate; in fact, they show an almost absent dormancy, as observable by their peculiarity to germinate immediately after the senescence of the fruit ( Figure 5 ). The effect of environmental factors, in particular temperature, light, and age, on seed germinability/dormancy is well documented ( Bhatt et al, 2016 ). These effects are also known to be reflected endogenously as changes in phytohormones levels, especially ABA and GA, that finally result in different timing of seed germinability/dormancy ( Chen et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Seeds from dark-developed capsules have not only a difference in mass but also in their tendency to germinate; in fact, they show an almost absent dormancy, as observable by their peculiarity to germinate immediately after the senescence of the fruit ( Figure 5 ). The effect of environmental factors, in particular temperature, light, and age, on seed germinability/dormancy is well documented ( Bhatt et al, 2016 ). These effects are also known to be reflected endogenously as changes in phytohormones levels, especially ABA and GA, that finally result in different timing of seed germinability/dormancy ( Chen et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, collected from different habitat of Qalyubia, Aswan, North coastal road and Saudi Arabia, small seeds of accessions R4, R8, R12 and R14 are also the more variegated colored seeds; larger greyscale values. This could be attributed to an increased levels of total phenolics that magnitude seed adaptation against hot climate habitat (23,25,26), or it may be adopted to increase seed persistence in the soil (27) (30). In accordance with the current finding Salihu and his coauthor on 2019 could not find a direct correlation between genetic diversity among 20 Nigerian castor genotypes and their geographical distribution (13).…”
Section: Discussionmentioning
confidence: 99%
“…Dark colored seeds in Pisum sativum L. (Atak et al 2008) and in Lotus sp. (Bhatt et al 2016) indicated that superior seed quality characteristics were observed in dark colored seeds than light ones. In contrary of these findings, light colored seeds had higher germination rate and lower EC values in Vigna subterranea L (Mandizvo and Odindo 2019) and in Cicer arietinum L. (Anuradha et al 2009.…”
Section: Intrоduсtiоnmentioning
confidence: 97%